The anti-apoptotic members of the Bcl-2 family are attractive tumor-associated antigens - thor Straten, Per (Impact Journals LLC, 2010)
Anti-apoptotic members of the Bcl-2 family (Bcl-2, Bcl-X(L) and Mcl-2) are pivotal regulators of apoptotic cell death. They are all highly overexpressed in cancers of different origin in which they enhance the survival of the cancer cells. Consequently, they represent prime candidates for anti-cancer therapy and specific antisense oligonucleotides or small molecule inhibitors have shown broad anti-cancer activities in pre-clinical models and are currently tested in clinical trials. In addition, immune-mediated tumor destruction is emerging as an interesting modality to treat cancer patients. Notably, spontaneous cellular immune responses against the Bcl-2 family proteins have been identified as frequent features in cancer patients underscoring that these proteins are natural targets for the immune system. Thus, Bcl-2 family may serve as an important and widely applicable target for anti-cancer immunotherapeutic strategies, alone or in the combination with conventional therapy. Here, we summarize the current knowledge of Bcl-2 family proteins as T-cell antigens, which has set the stage for the first explorative trial using these antigens in therapeutic vaccinations against cancer, and discuss future opportunities.